Immunity to Diphtheria and Tetanus in HIV-Infected Children - A.P. Volokha; I.V. Raus; B.Ye. Donskoy; L.I. Chernyshova; V.P. Chernyshov (Zaslavsky O.Yu., 2016)
Backgrоund. HIV infected patients are at risk for vaccine-preventable infections such as tetanus and diphtheria. It is important to know about the protection of HIV-infected children from these infections, as there is a risk even after complete immunization. The protective immunity after vaccination against diphtheria and tetanus is measured by the antibodies level against these pathogens. The aim of this study was to evaluate the persistence of immunity to tetanus and diphtheria toxoid in HIV-infected children. Materials and methods. The protective immunity against diphtheria and tetanus was studied in children with HIV infection in the Kyiv City AIDS Center. Immunization rate was evaluated in 142 HIV-infected children. Serum samples were obtained in 59 HIV-infected children (study group) vaccinated against diphtheria and tetanus toxoid during routine check-ups. The results of anti-tetanus and anti-diphtheria antibodies were compared with the data of 17 children without HIV (the control group). The mean age of HIV-infected patients was 9.2 years old (range from 1.6 to 15.5 years old). Most children (38/59, 64.4 %) had mild clinical manifestations of HIV infection (I and II clinical stage of the disease). 89.8 % (53/59) of children of the group received antiretroviral therapy. The level of CD4+ T-lymphocytes within age norms was in 88.2 % of children receiving ART. Results. The research revealed lower vaccination coverage of HIV-infected children against diphtheria and tetanus (63.3 %) than in the general population. Only 19.7 % (28/142) of HIV-infected children were fully vaccinated according to the National schedule against these bacterial infections. A large proportion of children with HIV infection (79.3 %) vaccinated against these pathogens does not have protective levels of antibodies against diphtheria. The protective level of antibodies against tetanus was absent in 28.8 % of vaccinated HIV-positive children. Mean level of tetanus antibodies in serum was significantly lower in HIV-infected children (0.28 IU/ml) compared to the children not infected with HIV (0.53 IU/ml), p < 0.001. The average serum level of antibodies against diphtheria was also significantly lower in HIV-infected children (0.22 IU/ml) compared to the children not infected with HIV (0.43 IU/ml), p < 0001. Only 18.6 % of children in the study group were protected against both pathogens compared with 41.2 % of children in the control group. HIV-infected children are not immune to diphtheria and tetanus and are at risk of these infections. Conclusions. The main predictor of immune protection against diphtheria and tetanus is an early treatment of HIV infection (in the first 2 years of life), higher levels of CD4 + T-cells at the beginning of ART and ART vaccination after being started on ART. We recommend controlling the level of specific antibodies HIV-infected children who have received vaccination against diphtheria and tetanus before the ART beginning. In case of the absence of protective antibodies an extra booster against these bacterial infections is recommended to HIV-infected children.